Development of Automated Facemask and Body Temperature System - Wahab, Nursyatirah; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2023)
We are all aware that Covid-19 has had a significant impact around the world. As a precaution, many countries have been placed on lockdown. We should use masks and sanitize ourselves frequently as one of the key measures to protect ourselves and society from Coronavirus. Now, the government is stepping forward to ease the lockdown in order to maintain society's financial balance. They have insisted on wearing a face mask before leaving our home, and the manual way of wearing masks by people is a difficult issue to monitor. Therefore, this work proposes a Face Mask Detection system to determine whether a person is wearing a mask and an infrared sensor to detect the person's thermal temperature. An app linked to that system will send him a warning to protect the community from the coronavirus. If a person works for a company and has registered with the appropriate application, and he is not wearing a mask and has thermal heat in his body. As a company employee, he will receive an alert on his own. If a camera records an unidentified face (Visitor's face), an alert will be issued directly to the company's authorities. A corporation has a feature that allows employees to obtain data that indicates the number of alerts sent to them by the Al alert notice with the person's photo. It enables the firm to enforce the use of the mask and monitor the person's thermal heat in order to prevent the coronavirus from spreading across the workplace.